Molecular Virology - Modrow, Susanne; Falke, Dietrich; Truyen, Uwe; Schätzl, Hermann (Springer Berlin Heidelberg : Imprint: Springer, 2013)
The book gives a comprehensive overview on the knowledge of virus infection relevant for humans and animals. For each virus family the molecular details of the virus particle and the viral replication cycle are described. In the case of virus types with relevance for human and/or animal health the data on molecular biology, genetics and virus-cell interaction are combined with those concerning, pathogenesis, epidemiology, clinics, prevention and therapy.